Morbidity and mortality after anaesthesia in early life: results of the European prospective multicentre observational study, neonate and children audit of anaesthesia practice in Europe (NECTARINE). (June 2021) - Disma, Nicola; Veyckemans, Francis; Virag, Katalin; Hansen, Tom G.; Becke, Karin; Harlet, Pierre; Vutskits, Laszlo; Walker, Suellen M.; de Graaff, Jurgen C.; Zielinska, Marzena; Simic, Dusica; Engelhardt, Thomas; et al.
Abstract: Background: Neonates and infants requiring anaesthesia are at risk of physiological instability and complications, but triggers for peri-anaesthetic interventions and associations with subsequent outcome are unknown. Methods: This prospective, observational study recruited patients up to 60 weeks' postmenstrual age undergoing anaesthesia for surgical or diagnostic procedures from 165 centres in 31 European countries between March 2016 and January 2017. The primary aim was to identify thresholds of pre-determined physiological variables that triggered a medical intervention. The secondary aims were to evaluate morbidities, mortality at 30 and 90 days, or both, and associations with critical events. Results: Infants ( n =5609) born at mean (standard deviation [sd] ) 36.2 (4.4) weeks postmenstrual age (35.7% preterm) underwent 6542 procedures within 63 (48) days of birth. Critical event(s) requiring intervention occurred in 35.2% of cases, mainly hypotension (>30% decrease in blood pressure) or reduced oxygenation (SpO2 <85%). Postmenstrual age influenced the incidence and thresholds for intervention. Risk of critical events was increased by prior neonatal medical conditions, congenital anomalies, or both (relative risk [RR]=1.16; 95% confidence interval [CI], 1.04–1.28) and in those requiring preoperative intensive support (RR=1.27; 95% CI, 1.15–1.41). Additional complications occurred in 16.3% of patients by 30 days, and overall 90-day mortality was 3.2% (95% CI, 2.7–3.7%). Co-occurrence of intraoperative hypotension, hypoxaemia, and anaemia was associated with increased risk of morbidity (RR=3.56; 95% CI, 1.64–7.71) and mortality (RR=19.80; 95% CI, 5.87–66.7). Conclusions: Variability in physiological thresholds that triggered an intervention, and the impact of poor tissue oxygenation on patient's outcome, highlight the need for more standardised perioperative management guidelines for neonates and infants. Clinical trial registration: NCT02350348 .